O43. Estimating the effectiveness of high LET radiations to induce damage to DNA in human lymphocytes and modelling the repair thereof. (September 2016) - Fourie, H.; Slabbert, J.P.; Belov, O.; Newman, R.; Panina, M.; Rossouw, N.
Abstract : Introduction: Neutron and ion beam irradiations have an increased efficiency in cell killing, resulting from their high linear-energy-transfer (LET) which in turn induces clustered and complex DNA breaks. Similarly, Auger electron irradiations have been shown to a have an increased relative biological effectiveness (RBE) when compared to low-LET radiations. We report on our investigations into the RBE of the DNA incorporated Auger electron emitting 123 I and a model which may estimate the induction and repair of γ -H2AX foci (markers of DNA double strand breaks (DSBs)) in human lymphocytes after exposure to fast neutrons. Materials and methods: The RBE of 123 I was determined by comparison of micronuclei inductions in T-lymphocytes using 5-[ 123 I]-iodo-2-deoxyuridine and similar inductions by graded doses of 60 Co γ -rays. Additionally, a theoretical model which describes the time-based repair pathways of DNA DSBs using a set of dependent partial differential equations, was investigated. The validity of the model was assessed by comparing the γ -H2AX foci kinetics predicted by the model to experimental curves observed for lymphocytes exposed to neutrons (20 keV/ μ m) and 60 Co γ -rays. Results: The dose-limiting RBE of the DNA incorporated 123 I was found to range from 3 to 11. These observed RBE values relate well to those obtained in studies with 125 I incorporated into rodent cell lines. The higher micronuclei frequencies noted for Auger electrons in the study is indicative of the high-LET nature of these particles. Similar to experimental observations, the theoretical repair model predicted that a larger number of DSBs remain unrepaired after neutron irradiation compared to low-LET γ -irradiation. The model was shown to accurately describe and estimate the kinetics of γ -H2AX foci in human lymphocytes after exposure to fast neutrons and 60 Co γ -rays. Conclusion: With respect to their role in radiation therapy and protection, there is a need for investigating and developing models which may predict the induction and repair of high-LET radiation induced DNA damage. Acknowledgement: This work was supported by a University Development Cooperation VLIR Own Initiative Programme between Belgium and South Africa.